Pengaruh Kepemimpinan dalam Motivasi Organisasi - Fitri Hayati; Anggun Sari Fadilla; Uswatun Hasanah Sitompul (Universitas Muhammadiyah Enrekang, 2022)
This study aims to determine how much influence leadership has on the motivation of an organization. Data collection uses reference collection methods in the form of reading materials such as books and scientific journal articles, which use a qualitative research approach. Many mistakes were made in running the organization, especially in terms of leadership, causing work targets not to be achieved because the HR workers did not get encouragement in the form of motivation from their leaders, thus reducing the integrity of the performance of employees which led to the destruction of the company or agency they led. The results of this study found that leadership has a major influence on organizational motivation because it will directly affect the performance results of employees and employee performance satisfaction so as to achieve the desired targets or those that have been determined by the organization.